1996
DOI: 10.1111/j.1365-2354.1996.tb00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in supportive care

Abstract: A range of distressing symptoms, such as nausea and vomiting, dyspnoea and pain, which invariably impair quality of life, may develop in cancer patients as a result of their disease and treatment. The side-effects of cancer treatments place additional burdens on the patient. Patients indicate that they find nausea and vomiting and fatigue to be the most distressing symptoms. The burden of distressing symptoms and the side-effects of cancer treatments may be so great for some patients that they make a decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…6 Adverse effects may be severe enough to impact on patients' decisions about continuing treatment. 7 With chemotherapy increasingly being administered in the ambulatory setting, patients need to be able to self-manage common adverse effects associated with their chemotherapy regimen and to know how to recognize signs that indicate the need for medical attention.…”
Section: Introductionmentioning
confidence: 99%
“…6 Adverse effects may be severe enough to impact on patients' decisions about continuing treatment. 7 With chemotherapy increasingly being administered in the ambulatory setting, patients need to be able to self-manage common adverse effects associated with their chemotherapy regimen and to know how to recognize signs that indicate the need for medical attention.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the adverse effects of chemotherapy (previously held to be unacceptable) are seen to be outweighed by the overall benefit to the patient of palliative chemotherapy, and the trade off argument can be said to have shifted in favour of this treatment. Improvements in the prevention and management of adverse effects associated with chemotherapy (such as emesis and infection) that contribute to improved quality of life and help to reduce the lengths of hospital stays also make palliative chemotherapy less of a burden for patients and help to shift the argument further (Redmond, 1996).…”
Section: Trade Off' In Cancer Chemotherapymentioning
confidence: 99%
“…Huge progress made in the treatment of cancer is not accompanied by the development of methods to prevent the unpleasant side effects of therapy [ 1 , 2 ]. According to the American Society of Clinical Oncology (ASCO) and the European Society for Medical Oncology (ESMO) guidelines [ 3 , 4 , 5 ], the most commonly chosen therapeutic options are radiotherapy and chemotherapy, as a monotherapy or as an adjuvant therapy with surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, patients suffer from mucositis, diarrhoea, constipation, nausea, and vomiting [ 7 ]. Alleviation of them is crucial to the improvement of patients’ comfort as they strongly influence therapy results [ 2 , 8 ]. It was suggested that probiotic administration may help to achieve this goal [ 9 ], particularly as they have shown a protective effect on epithelial cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%